High ankle-brachial index predicts cardiovascular events and mortality in hemodialysis patients with severe secondary hyperparathyroidism - Pichone,Alinie (2021)
Abstract Introduction: Vascular calcification related to severe secondary hyperparathyroidism (SHPT) is an important cause of cardiovascular and bone complications, leading to high morbidity and mortality in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD). The present study aimed to analyze whether ankle-brachial index (ABI), a non-invasive diagnostic tool, is able to predict cardiovascular outcomes in this population. Methods: We selected 88 adult patients on HD for at least 6 months, with serum iPTH>1,000pg/mL. We collected clinical data, biochemical and hormonal parameters, and ABI (sonar-Doppler). Calcification was assessed by lateral radiography of the abdomen and by simple vascular calcification score (SVCS). This cohort was monitored prospectively between 2012 and 2019 for cardiovascular outcomes (death, myocardial infarction (MI), stroke, and calciphylaxis) to estimate the accuracy of ABI in this setting. Results: The baseline values were: iPTH: 1770±689pg/mL, P: 5.8±1.2 mg/dL, corrected Ca: 9.7±0.8mg/dL, 25(OH)vit D: 25.1±10.9ng/mL. Sixty-five percent of patients had ABI>1.3 (ranging from 0.6 to 3.2); 66% had SVCS≥3, and 45% aortic calcification (Kauppila≥8). The prospective evaluation (51.6±24.0 months), provided the following cardiovascular outcomes: 11% of deaths, 17% of nonfatal MI, one stroke, and 3% of calciphylaxis. After adjustments, patients with ABI≥1.6 had 8.9-fold higher risk of cardiovascular events (p=0.035), and ABI≥1.8 had 12.2-fold higher risk of cardiovascular mortality (p=0.019). Conclusion: The presence of vascular calcifications and arterial stiffness was highly prevalent in our population. We suggest that ABI, a simple and cost-effective diagnostic tool, could be used at an outpatient basis to predict cardiovascular events in patients with severe SHPT undergoing HD.